1987
DOI: 10.1148/radiology.164.1.2954183
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term effects of massive balloon dilation on the aortic wall and vasa vasorum.

Abstract: To investigate the acute and long-term effects on the vasa vasorum after massive overdilation, canine aortic segments were dilated with Gruentzig balloon catheters to more than 100% over normal size. In the acute study, the significant lumen increase was the result of intimal and medial rupture with stretching and thinning of the adventitia. In these areas, the vasa vasorum were stretched and severed, causing adventitial hemorrhage. In the chronic study, areas of previous subtotal wall rupture with adventitial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 0 publications
3
14
0
2
Order By: Relevance
“…30 Previous studies have demonstrated that balloon angioplasty induces stretching and/or rupture of the vasa vasorum, with subsequent hemorrhage at the balloon site. 31 Occlusion of the vasa vasorum induces PDGF synthesis and intimal cell proliferation. 32 Ischemia/reperfusion of the vessel wall after angioplasty caused by occlusion of the vasa vasorum may set in motion a series of events leading to inflammation followed by the proliferation of adventitial and intimal cells.…”
Section: Discussionmentioning
confidence: 99%
“…30 Previous studies have demonstrated that balloon angioplasty induces stretching and/or rupture of the vasa vasorum, with subsequent hemorrhage at the balloon site. 31 Occlusion of the vasa vasorum induces PDGF synthesis and intimal cell proliferation. 32 Ischemia/reperfusion of the vessel wall after angioplasty caused by occlusion of the vasa vasorum may set in motion a series of events leading to inflammation followed by the proliferation of adventitial and intimal cells.…”
Section: Discussionmentioning
confidence: 99%
“…46 It is now well established that oxygen tension has profound effects on the wound repair response, such that hypoxia induces inflammatory and other mesenchymal cells to secrete growth factors that directly influence proteinase synthesis in cells at the wound site. 33 .…”
Section: Implications Of Proteinase and Inhibitor Location In Aortic mentioning
confidence: 99%
“…In the aortic wall, proliferation of the vasa vasorum is a characteristic feature observed during the repair response to dilation. 46 Neovascularization is known to be associated with both metalloproteinase (CL, GL, and stromelysin) and serine proteinase (tissue plasminogen activator) synthesis and secretion. 32 Induced capillary endothelial cells also secrete large quantities of TIMP.…”
Section: Implications Of Proteinase and Inhibitor Location In Aortic mentioning
confidence: 99%
“…Within the wall of the host blood vessel, a network of microvessels is formed, the vasa vasorum. Despite lying predominantly in the adventitia, in certain large arteries, veins, and atherosclerotic arteries, these microvessels also penetrate the media [2][3][4]. They constitute nutrient vases within the wall of most arteries, including the aorta and coronary arteries, carotids, and femoral arteries [5,6], as well as within some intracerebral arteries and the vena cava [7,8].…”
Section: Introductionmentioning
confidence: 99%